Optimizing Internal Supervision: The Role of Time and Location in Enhancing Health Center Service Quality in Kendari - Fadilah, Fadilah; Asri, Andi; Munir, Sanihu (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction: The problem in this study is the data on the achievement of health center accreditation in Kendari City, namely: 10 intermediate health centers (66%), 2 basic (13%), 2 main (13%) and 1 plenary (6.6%). This data indicates that not all health centers have implemented service standards according to PMK 46 of 2015 concerning Health Center Accreditation Standards, this condition provides an illustration that technical guidance and supervision carried out at the Health Center have not been carried out optimally. The purpose of this study was to analyze the relationship between internal supervision strategies and improving the quality of health services as a managerial function at the Kendari City Health Center. Method: This type of research is quantitative Observational using Cross Sectional Study design. The population of the study were all health center leaders, Personal Health Efforts managers, Public Health Efforts managers and quality managers totaling 60 people at Kendari City health centers. The sampling method used the Total Sampling technique. Result: The results of the chi-square test on the supervision time variable obtained a value of X2 hit = 17.019, the location of supervision obtained a value of X2 hit = 13.081. Conclusion: There is a relationship between the time of supervision and the location of supervision with the improvement of service quality at the Kendari City Health Center.